2022
DOI: 10.22353/mjbs.2022.20.04
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution tolerance indices of selected plants around Ulaanbaatar city, Mongolia

Abstract: This study examined the air pollution tolerance index (APTI) of six plant species (two trees and four herbs) from Ulaanbaatar city (polluted site) and unpolluted area (control site). APTI values for Orostachys spinosa (L.) C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Over and above this, NBS have been shown to improve human mental and physical health and well-being (Ascenso et al, 2021), and when designed and implemented in a participatory manner, can favourably benefit women, youth and low-income communities (Pagano et al, 2019;Bechauf, 2021). Nature-based solutions can also be used as effective biomonitoring tools to determine the presence, quantities, temporal or spatial changes and effects of pollutants on the environment (Calfapietra, 2020;Fusaro et al, 2021;Shagjjav et al, 2022). For example, a study by Molnár et al, (2020) which assessed the usefulness of an Air Pollution Tolerance Index for environmental health, particularly considering air quality, showed that quantifying the amount of deposited dust on the surface of urban tree leaves can be an effective method for monitoring urban air quality.…”
Section: Nature-based Solutions For Urban Resiliencementioning
confidence: 99%
“…Over and above this, NBS have been shown to improve human mental and physical health and well-being (Ascenso et al, 2021), and when designed and implemented in a participatory manner, can favourably benefit women, youth and low-income communities (Pagano et al, 2019;Bechauf, 2021). Nature-based solutions can also be used as effective biomonitoring tools to determine the presence, quantities, temporal or spatial changes and effects of pollutants on the environment (Calfapietra, 2020;Fusaro et al, 2021;Shagjjav et al, 2022). For example, a study by Molnár et al, (2020) which assessed the usefulness of an Air Pollution Tolerance Index for environmental health, particularly considering air quality, showed that quantifying the amount of deposited dust on the surface of urban tree leaves can be an effective method for monitoring urban air quality.…”
Section: Nature-based Solutions For Urban Resiliencementioning
confidence: 99%